Effect of topical heparin and levomenol on atopic dermatitis: a randomized four-arm, placebo-controlled, double-blind clinical study - Arenberger, P; Arenbergerová, M; Drozenová, H; Hladíková, M; Holcová, S (Journal of the European Academy of Dermatology and Venereology, 2011)
BACKGROUND: The aim of the controlled double-blind trial was to demonstrate the superiority of a topical combination product over its single constituents. PATIENTS AND METHODS: A total of 278 patients with atopic dermatitis were randomized into four groups: 79 patients were treated with a topical combination of levomenol and heparin (A), 80 patients with levomenol alone (B), 78 patients with heparin alone (C) and 41 patients with the cream base with no active substances (D). The medication was applied twice daily for 8weeks. Efficacy criteria included the severity of pruritus (visual analogue scale, VAS) and the SCORing Atopic Dermatitis (SCORAD) index as well as the overall assessment of efficacy and tolerance by both physician and patient. RESULTS: The improvement of pruritus and SCORAD values in Group A was significantly higher compared with Groups B-D (ancova, P<7×10(-8) ). The improvement of pruritus in Group A approximately corresponded to the cumulative effect of the two single active substances, with mean improvements of itching of -41.3, -13.3, -21.3 and +0.6mm VAS in Groups A-D, respectively (95% CI 7.1-13.5, 2.9-9.2 and 10.4-18.3mm for the comparisons A vs. B, A vs. C and A vs. D). CONCLUSION: The combination of levomenol and heparin proved to be significantly more efficacious in the treatment of pruritus and inflamed skin than the preparations of the single components.
Keywords: Infant; dospělí; Double-Blind Method; Sesquiterpenes; pruritus; předškolní dítě; Humans; lidé středního věku; Middle Aged; Fibrinolytic Agents; Administration, Cutaneous; seskviterpeny; mladý dospělý; Dermatitis, Atopic; Patient Satisfaction; Heparin; mužské pohlaví; fibrinolytika; fixní kombinace léků; aplikace kožní; Monocyclic Sesquiterpenes; Severity of Illness Index; stupeň závažnosti nemoci; Child, Preschool; Drug Combinations; Adult; Adolescent; monocyklické seskviterpeny; spokojenost pacientů; ženské pohlaví; heparin; Pruritus; atopická dermatitida; lidé; mladiství; dítě; Child; Male; Young Adult; kojenec; dvojitá slepá metoda; Female